YENİ İLKÖĞRETİM BİRİNCİ KADEME PROGRAMLARININ UYGULAMADAKİ ETKİLİLİĞİNİN DEĞERLENDİRİLMESİ - BULUT, İLHAMİ (Fırat Üniveristesi, 2006)
Araştırmanın genel amacı, 2004-2005 Öğretim Yılında İlköğretim BirinciKademe Yeni Programlarının (Türkçe, Matematik, Hayat Bilgisi, Fen ve Teknoloji,Sosyal Bilgiler) uygulamadaki etkililiğini belirlemektir. Bunun için 2004-2005 ÖğretimYılında yeni programların uygulandığı İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay,Samsun ve Bolu illerindeki deneme okullarında araştırma yapılmıştır.Araştırmada betimsel tarama (survey) modeli kullanılmıştır. Güvenirlik vegeçerlilik hesaplamalarından sonra geliştirilen veri toplama araçları, İstanbul, Ankara,İzmir, Kocaeli, Van, Hatay, Samsun ve Bolu illerindeki deneme okullarında görevyapan toplam 982 sınıf öğretmenine uygulanmıştır.Araştırmada elde edilen bulgular şöyle özetlenebilir;Yeni Türkçe dersi öğretim programında öngörülen kazanımların, kapsamınve eğitim durumunun uygulamada ?çok?, programda öngörülen değerlendirmenin ise?orta? düzeyinde etkili olduğu görülmüştür. Yeni Matematik dersi öğretimprogramında öngörülen kazanımların, kapsamın ve eğitim durumunun uygulamada?çok?, programda öngörülen değerlendirmenin ise ?orta? düzeyinde etkili olduğugörülmüştür. Yeni Hayat Bilgisi dersi öğretim programında öngörülen kazanımların,kapsamın, eğitim durumunun ve değerlendirmenin uygulamada ?çok? düzeyinde etkiliolduğu görülmüştür. Yeni Fen ve Teknoloji dersi öğretim programında öngörülenkazanımların, kapsamın, eğitim durumunun ve değerlendirmenin uygulamada ?çok?düzeyinde etkili olduğu görülmüştür. Yeni Sosyal Bilgiler dersi öğretim programındaöngörülen kazanımların, kapsamın, eğitim durumunun ve değerlendirmenin uygulamada?çok? düzeyinde etkili olduğu görülmüştür.Anahtar Kelimeler: Yeni İlköğretim Programları, Program Değerlendirme,Yapılandırmacılık, Öğrenci Merkezlilik.ABSTRACTAn Evaluation of the Effectiveness of the New Primary School Curricula inPracticeİlhami BULUTFırat UniversityInstitute of Social SciencesDepartment of Educational SciencesFebruary-2006, Page:XL+445The main aim of this study is to determine the effectiveness of the New PrimaryEducation Curricula (Turkish Language, Mathematics, Teaching Life, Science andTechnology and Social Studies) in practice conducted in 2004-2005 academic year. Theresearch was conducted in pilot schools İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay,Samsun and Bolu cities where the New Primary Education Curricula were piloted in2004-2005 academic year.This is a descriptive study. After reliability and validity analyses, the datacollection tools were administered to 982 primary school teachers working in pilotschools in İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay, Samsun and Bolu cities.The findings of the study can be summarized as follows.It was determined that the learning attainments, content and learning environment in theNew Turkish Curriculum were adopted at ?much? level, while measurement andevaluation was adopted at ?middle? level. It was also determined that the learningattainments, content and learning environment in the New Mathematics Curriculumwere adopted at ?much? level, while measurement and evaluation was adopted at?middle? level. It was seen that the learning attainments, content and learningenvironment and measurement and evaluation in the New Teaching Life Curriculumwere adopted at ?much? level. It was also seen that the learning attainments, contentand learning environment and measurement and evaluation in the New Science andTechnology Curriculum were adopted at ?much? level. It was also determined from thecurrent research that the learning attainments, content, learning environment andmeasurement and evaluation in the New Social Studies Curriculum were adopted at?much? level by the teachersKey Words: New Primary School Curricula, Curriculum Evaluation, Constructivism,Student-centered instruction.

XABSTRACTAn Evaluation of the Effectiveness of the New Primary School Curricula inPracticeİlhami BULUTFırat UniversityInstitute of Social SciencesDepartment of Educational SciencesFebruary-2006, Page:XL+445The main aim of this study is to determine the effectiveness of the New PrimaryEducation Curricula (Turkish Language, Mathematics, Teaching Life, Science andTechnology and Social Studies) in practice conducted in 2004-2005 academic year. Theresearch was conducted in pilot schools İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay,Samsun and Bolu cities where the New Primary Education Curricula were piloted in2004-2005 academic year.This is a descriptive study. Different data collection tools were developed foreach curriculum in order to asses the effectiveness of the curricula. Data collection toolsthat were developed by taking into consideration the curriculum evaluation model,consisting of items as aims, contents, instructional processes and measurement andevaluation, were administered to 124 teachers in five pilot schools in Diyarbakır citycenter for reliability and validity analyses. After reliability and validity analyses, thedata collection tools were administered to 982 primary school teachers working in pilotschools in İstanbul, Ankara, İzmir, Kocaeli, Van, Hatay, Samsun and Bolu cities. Thefindings of the study can be summarized as follows;
An evaluation of the effectiveness of the new primary school curricula in practice
Keywords: Eğitim ve Öğretim